Pemodelan bawah permukaan zona subduksi Daerah Selatan Jawa Barat berdasarkan data anomali medan gravitasi - Muhammad Isom Ashar; Muhammad Irham Nurwidiyanto; Hernowo Danusaputro (Youngster Physics Journal, 2017)
The southern part of western Java is a subduction path between the Indo- Australian plate and Eurasian plate which still active. Subduction paths can also be identified by geophysical methods. One of geophysics method that can be used is the gravity method. The gravity method can describe the form of subsurface rocks based on the variations of the earth's gravitational field which generated by differences in density (mass density) between rocks. This research was conducted to know the condition of subsurface by doing 2D modeling. Anomaly data obtained from bgi.omp.obs. At the regional anomaly, 2D modeling was performed showing the rock density and there is subduction in the south of West Java. The rock ocean plate has a density of 3.14 g/cm 3. Continental plate has a density of 2.51 g/cm 3,the rock which has been deformed has a density of 2.29 g/cm 3, sedimentary rock has density 2.11 g / cm 3 and bedrocks have density 2.36 g/cm 3. From the subduction model can be sloped between 11o to 13oKeywords: Subduction, West Java, Gravity method, Density